Social Media and Civil Society in the Governor’s Election of North Sumatera 2018 - Dedi Sahputra; Indra Muda; Taufik Wal Hidayat; Waridah Waridah (Ikatan Sarjana Komunikasi Indonesia, 2020)
The phenomenon of democratization, civil society and the use of social media in North Sumatra found its momentum in the North Sumatra Gubernatorial Election (Pilkada) 2018. This study uses a qualitative descriptive method by presenting descriptive data about the civil society movement that uses social media in the North Sumatra Gubernatorial Election. The results of the research show that the emergence of functional civil society movement has given different colors to local politics in North Sumatra. The movement that served as a means of channeling the community’s aspirations, has become a driving factor for the victory of one of the candidates for North Sumatra governor in 2018. The use of social media as a means of interaction, communication, and information forms a pattern in new social movement.